2018
DOI: 10.3390/su10061713
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability in Smart Farms: Its Impact on Performance

Abstract: In Spain, more than 30% of producers have run out of business because of a lack of sustainability. They search for managerial guidelines that allow them to reach the farm's economic viability. When trying to improve the performance of farms and farming systems, a complementary consideration of sustainability dimensions is required. The aim of this paper consists of offering a complementary and integrative approach from the sustainability concept in four different dimensions: economic; technological; organizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 36 publications
0
22
0
Order By: Relevance
“…They indicate that producers should increase dimension at a great extent, otherwise a significant number of smallholders will be expelled from the system and will have to become laborers in their community or migrate to urban areas to find employment [32]. The increase of scale and intensification is an important aspect, although it is not enough for reaching a sustainable development in the tropics [2,7,10,11,17]. Our results showed that size was not associated to technological level.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…They indicate that producers should increase dimension at a great extent, otherwise a significant number of smallholders will be expelled from the system and will have to become laborers in their community or migrate to urban areas to find employment [32]. The increase of scale and intensification is an important aspect, although it is not enough for reaching a sustainable development in the tropics [2,7,10,11,17]. Our results showed that size was not associated to technological level.…”
Section: Discussionmentioning
confidence: 62%
“…The research is exploratory and further research evaluating the incidence of technologies in the results through logistic regression, structural equation model (SEM); identifying the causes of inefficiencies with DEA, etc. [6,7,9,10] should be done.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their research suggests that farms face tremendous challenge of failing sustainability. By reference to selected case-studies from Spain, the authors suggest how the challenge can be bypassed [19]. Certainly, smart villages and the production process is not only about farming.…”
Section: How To Promote Socio-economic Sustainability In the Smart VImentioning
confidence: 99%
“…In Spain, the dairy sheep industry suffers from an intense crisis as a consequence of a group of factors: lack of profitability, increased bureaucracy in management, absence of intergenerational relay that assures the continuity of the activity [1][2][3], changes in the habits of consumers with a reduction in the consumption of sheep meat and animal protein [4], and the need to mitigate climate change and reduce greenhouse gas emissions [5]. In Castilla La Mancha (central Spain), the producers have responded to the crisis: 33.7% of farms have abandoned the milking activity and the rest show a trend towards the intensification and specialization of production [6].…”
Section: Introductionmentioning
confidence: 99%